Simulasi Citra Nasionalis Melalui Fashion: Studi Kasus Batik Printing dalam Gaya Hidup Post Modern Masyarakat Kota - Oscario, Angela (Humaniora, 2014)
Batik printing, especially imported batik printing has threatened Indonesian handwritten batik and Indonesian stamp batik. Batik printing, that from the point of view of post-modern aesthetic is called pastiche, is an imitation of Batik that lack of authenticity and orisinality. Ironically, Indonesian people, especially those who live in Jakarta and who always want to preserve Indonesian culture by wearing batik, are often wearing imported Batik printing. This allegedly occurred because majority of people who live in Jakarta are always searching for an identity. They are new comers that come from many Indonesian areas; that had already lost bonding with their origin areas. Therefore they easily fallen into imitation that can provide identitiy –eventhough it’s only an artificial identity- such as batik printing. Batik printing is able to provide an artificial identity by stimulating a nationalist image. People didn’t realize they have been living in fatamorgana of post-modern era. In this era, image becomes very dominant. It constructs reality, an illusive reality. People in Jakarta become concerned only with appearance and style. They have merged into a massive consumption.